Literature Review: The Effect of Progressive Muscle Relaxation Technique on Dysmenorrhea In Adolescent Girls - Viani, Zalestya; Yulizawati, Yulizawati; Hardisman, Hardisman; Halida, Erda Mutiara; Fitria, Henni (Universitas Andalas, 2025)
Dysmenorrhea is menstrual pain that can interfere with activities. Primary dysmenorrhea is a condition that occurs due to changes in prostaglandin hormone levels. In Indonesia, the prevalence of primary dysmenorrhea in 2019 was 54.89%. Dysmenorrhea can be alleviated through non-pharmacological methods, one of which is the progressive muscle relaxation technique, which has no side effects. This study aim to examine the effect of progressive muscle relaxation techniques in reducing primary dysmenorrhea. This study was a literature review using the scoping review method, conducted from April 2024 to February 2025. Data was collected from databases (PubMed, ScienceDirect, Google Scholar, and GARUDA) with publications from 2019 to 2024. The data analysis was carried out using thematic analysis. The selected articles were organized into a PRISMA-ScR (Preferred Reporting Items for Systematic Review and Meta-Analyses extension for Scoping reviews) flow diagram, resulting in 15 analyzed articles. The research results indicate that progressive muscle relaxation techniques have an effect on reducing primary dysmenorrhea. However, factors such as stress experienced by women during relaxation exercises and an unconducive environment may affect the success of the technique